THE STATE OF BONE METABOLISM AT NON-CALCULOUS CHRONIC CHOLECYSTITIS IN PATIENTS WITH ARTERIAL HYPERTENSION - Pasiyeshvili, L. M.; Andrusha, A. B.; Rezunenko, O. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The state of the bone tissue in patients with chronic noncalculous cholecystitis (CNC) and arterial hypertension (AH) was assessed by biochemical markers of bone remodeling. It was established that in this comorbidity notices a reduction of bone isoenzyme of alkaline phosphatase (at 36,6 %) — a marker of bone formation against the background of increasing of tartrate acid phosphatase — isoenzyme, which used to assess of bone resorptive processes. Moreover, these changes were associated with a duration of CNC, with the type of gallbladder dyskinesia, sex and stage of AH.